Author Correction: Identifying long-term stable refugia for relict plant species in East Asia. Issue 1 (December 2018) - Tang, Cindy; Matsui, Tetsuya; Ohashi, Haruka; Dong, Yi-Fei; Momohara, Arata; Herrando-Moraira, Sonia; Qian, Shenhua; Yang, Yongchuan; Ohsawa, Masahiko; Luu, Hong; Grote, Paul; Krestov, Pavel; et al.
In the original version of this Article, an incorrect sample size was provided for the number of relict species (443 instead of 442) and the number of relict forests (423 instead of 422). These errors have been corrected in both the PDF and HTML versions of the Article.